Responsible Research and Innovation: conception, emergence and challenges for implementation - Zanin, Maria; Arruda, Adriana Goncalves; Rothberg, Danilo [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2021)
Currently, there is a demand to produce science in a participatory way, since agents of society - researchers, legislators, politicians, educators, entrepreneurs and citizens - must be involved in the scientific production process (from the construction of the agenda to the completion of the project and results) in order to foster the construction of a responsible society with the future. The challenges arising from this context have been object of theoretical approaches to Research and Responsible Innovation, which article describes, examines and contextualizes in the current scenario. The methodology includes bibliometric and bibliographic reviews, used in order to understand the dissemination of the term in the English and Portuguese (Brazil) languages, in addition to rescuing the context of the RRI, exploring its concepts and principles. We sought to reflect on the challenges of implementing RRI in Brazil. It is expected to contribute to the RRI dialogue in the country and to raise reflections on the importance of applying it to agents and initiatives responsible for the socioeconomic and environmental spheres.
Keywords: Responsible Research and Innovation; Public engagement with science; Science; Technology and Innovation; Technology and Society; Public policy